New Hampshire Community Loan Fund : a nonprofit attempts to change the financial equation for manufactured homes - Oster, Sharon M., (SAGE knowledge. Cases., 2016)
For Americans who cannot afford a standard home mortgage, one alternative to renting an apartment is to buy a mobile home. Also known as manufactured housing, mobile homes are built in a factory and then transported by tractor-trailer to the site where they will be occupied. They provide permanent housing at prices that are less than half the cost per square foot of regular 'site-built' houses. But although manufactured homes offer an affordable way to own a house, they also come with some special challenges. This case study discusses these challenges.